A Microbiome DNA Enrichment Method for Next‐Generation Sequencing Sample Preparation. Issue 1 (1st July 2016) - Yigit, Erbay; Feehery, George R.; Langhorst, Bradley W.; Stewart, Fiona J.; Dimalanta, Eileen T.; Pradhan, Sriharsa; Slatko, Barton; Gardner, Andrew F.; McFarland, James; Sumner, Christine; Davis, Theodore B.
Abstract: "Microbiome" is used to describe the communities of microorganisms and their genes in a particular environment, including communities in association with a eukaryotic host or part of a host. One challenge in microbiome analysis concerns the presence of host DNA in samples. Removal of host DNA before sequencing results in greater sequence depth of the intended microbiome target population. This unit describes a novel method of microbial DNA enrichment in which methylated host DNA such as human genomic DNA is selectively bound and separated from microbial DNA before next‐generation sequencing (NGS) library construction. This microbiome enrichment technique yields a higher fraction of microbial sequencing reads and improved read quality resulting in a reduced cost of downstream data generation and analysis. © 2016 by John Wiley & Sons, Inc.